1993
DOI: 10.1007/bf00004572
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and IGF-I receptors and tyrosine kinase activity in carp ovaries: changes with reproductive cycle

Abstract: Insulin and insulin-like growth factor I (IGF-I) receptors from carp ovaries were semipurified with wheat germ agglutinin at different moments of the reproductive cycle and their binding characteristics and tyrosine kinase activity were studied. Specific receptors for insulin and IGF-I were found. IGF-I receptors presented higher binding (23.8 ± 1.5%), number of receptors (965 ± 20fm/mg) and affinity (KD 0.24 ± 0.03nM) than those shown for insulin receptors (4.1 ± 1%, 530 ± 85fm/mg and 0.85 ± 0.1nM, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…It is expressed in an autocrine/paracrine manner in other tissues and organs (Rinecke et al 1997;Mommsen 1998;Perrot et al 1999;Biga et al 2004). Circulating IGF-I levels seem to play an important role in growth regulation in fish (Moriyama et al 1994;Duan 1997;Dyer et al 2004), and the possibility that IGF-I may have a role in the regulation of gonadal function is supported by presence of IGF-I receptors in fish ovary at different reproductive stages (Gutierrez et al 1993;Maestro et al 1997;Perrot et al 2000). Further evidence of this regulatory role is provided by the ability of fish ovary to produce IGF-I (Duan et al 1993;Duguay et al 1994;Kagawa et al 1995;Reinecke et al 1997;Schmid et al 1999;Biga et al 2004) and the presence of circulating IGF-I in sexually mature fish .…”
Section: Introductionmentioning
confidence: 93%
“…It is expressed in an autocrine/paracrine manner in other tissues and organs (Rinecke et al 1997;Mommsen 1998;Perrot et al 1999;Biga et al 2004). Circulating IGF-I levels seem to play an important role in growth regulation in fish (Moriyama et al 1994;Duan 1997;Dyer et al 2004), and the possibility that IGF-I may have a role in the regulation of gonadal function is supported by presence of IGF-I receptors in fish ovary at different reproductive stages (Gutierrez et al 1993;Maestro et al 1997;Perrot et al 2000). Further evidence of this regulatory role is provided by the ability of fish ovary to produce IGF-I (Duan et al 1993;Duguay et al 1994;Kagawa et al 1995;Reinecke et al 1997;Schmid et al 1999;Biga et al 2004) and the presence of circulating IGF-I in sexually mature fish .…”
Section: Introductionmentioning
confidence: 93%
“…In teleosts, as in mammals, IGF-I is mainly produced by the liver under the control of GH (Funkenstein et al 1990, Shamblott et al 1995, Duguay et al 1996 and plays, with GH itself, an important role in regulating body growth (see reviews by Chan & Steiner 1994, Plisetskaya et al 1994. Some data also suggest that IGF-I may participate in the direct regulation of the gonads in teleosts (Duguay et al 1992, Duan et al 1993, Gutiérrez et al 1993, Kagawa et al 1995, and review by Le Gac et al 1993), as it does in mammals (Hansson et al 1989, Monniaux & Pisselet 1992, and review by Giudice 1992). As to its central actions, an inhibitory effect on GH secretion was demonstrated in the rainbow trout (Oncorhynchus mykiss) (Pérez-Sànchez et al 1992, Blaise et al 1995 and in the European eel (Anguilla anguilla) , indicating a classical negative feedback on the somatotrophic axis, as in mammals (Berelowitz et al 1981, Yamashita & Melmed 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the similarity of rsIGF-I and rhIGF-I in their biological activity will be reflected in receptor-binding. In our pilot experiments using purified IGF-I receptor preparations (GutiCrrez et al, 1993) from either coho salmon or rat heart muscle we found similar specific binding of recombinant coho salmon and human IGF-I tracers. The average maximum binding to receptors in coho salmon heart preparations was 16.7% and 21.7% (n = 3) and in the rat heart preparation 3% and 2.3% for rsIGF-I and rhIGF-I tracers, respectively.…”
Section: Discussionmentioning
confidence: 54%